2015
DOI: 10.2169/internalmedicine.54.0267
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis-related Portal-Systemic Encephalopathy

Abstract: Hemodialysis-related portal-systemic encephalopathy (HRPSE) is characterized by the presence of portosystemic encephalopathy without liver dysfunction, usually caused by changes in the systemic venous flow related to hemodialysis. We herein describe the case of a 75-year-old woman who developed hepatic encephalopathy five years after the initiation of hemodialysis. Abdominal contrast-enhanced computed tomography (CT) and three-dimensional CT angiography revealed a portosystemic venous shunt, and the patient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…また血液透析とPSSによる高アンモニア血症の関係については様々な報告があり,一貫して血液透析での除水量が多いことが脳症の増悪因子になるとされている 15), 16), 17)。急激な除水で体循環系の静脈圧と門脈圧に圧較差が生まれ,PSSの血流を増やすというのがその理由である。本症例では再入院後にaHUS再燃による腎不全に対して血液透析を施行したが,2日間大きく除水した後しばらくしてアンモニア値の急上昇と意識障害が出現しており(Fig. 3, 4),血液透析による急激な除水が高アンモニア血症に悪影響を及ぼしていた可能性がある。…”
Section: 考  察unclassified
“…また血液透析とPSSによる高アンモニア血症の関係については様々な報告があり,一貫して血液透析での除水量が多いことが脳症の増悪因子になるとされている 15), 16), 17)。急激な除水で体循環系の静脈圧と門脈圧に圧較差が生まれ,PSSの血流を増やすというのがその理由である。本症例では再入院後にaHUS再燃による腎不全に対して血液透析を施行したが,2日間大きく除水した後しばらくしてアンモニア値の急上昇と意識障害が出現しており(Fig. 3, 4),血液透析による急激な除水が高アンモニア血症に悪影響を及ぼしていた可能性がある。…”
Section: 考  察unclassified
“…To the best of our knowledge, most of the previous studies focused on the fetal HVS shunts [9][10][11][12][13][14], only a few studies reported their variants [15]. The variants of fetal HVS have not been systemically described before.…”
Section: Introductionmentioning
confidence: 99%